2019
DOI: 10.1186/s12917-019-1990-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular epidemiology of methicillin resistant Staphylococcus pseudintermedius strains isolated from canine clinical samples in Argentina

Abstract: Background Staphylococcus pseudintermedius is the leading cause of pyoderma in dogs and the frequent use of antimicrobial treatment is associated to the development of resistance to nearly all classes of antibiotics. Despite S. pseudintermedius significance, our understanding of the molecular mechanism of β-lactam resistance and its genetic diversity remains limited. We aimed to: i ) determine the phenotypic resistance profile of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 45 publications
4
31
0
1
Order By: Relevance
“…Systemic and topical antibiotics are currently used to treat superficial and deep canine staphylococcal pyoderma, but longterm treatments are required and most animals suf-fer from recurrent infections [5]. Today, the development of antibiotic resistance in the causative bacteria is an important problem in veterinary medicine and public health, especially methicillin-resistant S. pseudintermedius [6].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic and topical antibiotics are currently used to treat superficial and deep canine staphylococcal pyoderma, but longterm treatments are required and most animals suf-fer from recurrent infections [5]. Today, the development of antibiotic resistance in the causative bacteria is an important problem in veterinary medicine and public health, especially methicillin-resistant S. pseudintermedius [6].…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in our study, 73.6% (19 cases) of isolates corresponding to S. pseudintermedius were presumptive to carry the mec gene. Interestingly, it has been found that S. pseudintermedius from companion animals was the causative agent of infection in humans (9,11,12,16,56), highlighting the importance of considering those isolates found in the present study as potential zoonotic agents. On the other hand, the SCCmec is a complex element.…”
Section: Discussionmentioning
confidence: 68%
“…Other bacterial species found in healthy skin of dogs are S. aureus, S. schleiferi (6), and Pseudomonas aeruginosa (7). Because S. pseudintermedius occasionally colonizes the human skin causing bacterial dermatitis, it has been proposed and evidenced as a zoonotic bacterium transmitted from the dog to their owner (8)(9)(10)(11)(12). One critical problem in clinical settings requiring confirmatory phenotyping of staphylococci causing CSP is the inability to differentiate between S. aureus and S. pseudintermedius because of the lack of differentiation tests between these two species (13), which can result in incorrect diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations